Nest predation of woodland birds in south-east Australia: importance of unexpected predators. (2nd January 2017) - Guppy, Michael; Guppy, Sarah; Marchant, Richard; Priddel, David; Carlile, Nicholas; Fullagar, Peter
ABSTRACT: For most passerines, nest predation has a major impact on breeding success; however, information on the identity of nest predators is scant. In 2012, we investigated the identity of nest predators that each year depredate about 50% of the nests of 21 species in a south-east coastal bird community in New South Wales, Australia. The current study is a 2-year extension of this study and shows that at this study site (a) predation accounts for at least 90% of nest failures, (b) identified nest predators comprised two reptiles, nine birds and five mammals, (c) the suite of predators changes each season, (d) the two major predators were the Eastern Whipbird ( Psophodes olivaceus ) and the Fan-tailed Cuckoo ( Cacomantis flabelliformis ), (e) the impact of the Red Fox and Feral Cat was minimal, and (f) there was a variable and complex interaction between the parasitic cuckoos and their hosts. The data show definitively the overwhelming importance of nest predation on fledgling production, and bring to light new and important data on several aspects of the suite of nest predators.